Selective laser melting of Al-12Si alloy: Enhanced densification via powder drying - Li, X.; O'Donnell, Kane; Sercombe, T. (2016)
Unlike conventional powder metallurgy techniques, selective laser melting (SLM) is characterised by its fully melting process and very high heating and cooling rates and little has been known about the influence of powder surface state on the SLM process. In this study, the influence of low temperature powder drying on the surface chemistry of Al-12Si powder and its subsequent effect on SLM was investigated in detail by means of an in-depth X-ray photoelectron spectroscopy. An enhanced densification (relative density =99%) was achieved in the dried Al-12Si powder compared to the as-received powder. This has been attributed to the modification of powder surface by removing a moisture skin during the drying process, which prevents the formation of deleterious oxide and hydroxide during SLM. This study provides important information for achieving high relative density in SLM fabricated metal components from a powder drying aspect.